Macroscopic Hematuria due to Placenta Percreta: Report of Two Cases and Short Review - Ourania Koukoura; George Lialios; Antonios Garas; George Sveronis; Asterios Nidimos; Irondiana Gkorezi; Zoi Alevra; Vassilios Tzortzis; Athanasios Oeconomou; Ioannis Zachos; Alexandros Daponte (Case Reports in Obstetrics and Gynecology)
Herein we present two cases of pregnant women with placenta percreta and severe hematuria during the 24th and 35th weeks of pregnancy, respectively. A timely sonographic diagnosis was feasible in the first case and cesarean section was performed during the 29th week. During the operation, the placenta was invading the bladder wall and concomitant hysterectomy with cystotomy and bladder wall reconstruction was performed. The second case presented in our emergency department with vaginal bleeding during the 35th weeks of pregnancy. She underwent an emergency cesarean section with uterine preservation, cystotomy, and bladder reconstruction.